Pluralisme Kepemimpinan dalam Sudut Pandang Muhammadiyah - Rifqi Andika Ramadhan (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The purpose of this paper is to try to provide an explanation of pluralism from the viewpoint of Muhammadiyah. In this study using qualitative research methods with a descriptive approach through library research, which is a way of systematically analyzing existing literature such as articles, books, journals and documents related to research themes so that the data obtained is valid and authentic. This study concludes that the progress of the Muhammadiyah Organization is inseparable from the participation of Muhammadiyah cadres as leaders and the differences in the leadership model in Ortom/AUM, there are no statements or interventions given by Persyarikatan Muhammadiyahas long as he does not violate the rules of Islam and remains firm with the principles of the Qur'an and As-Sunnah, as well as making the Rasulullah S.A.W his role model in leadership.